Study of JavaScript Static Analysis Tools for Vulnerability Detection in Node.js Packages - Brito, Tiago; Ferreira, Mafalda; Monteiro, Miguel; Lopes, Pedro; Barros, Miguel; Santos, Jose Fragoso; Santos, Nuno (IEEE transactions on reliability, 2023)
With the emergence of the Node.js ecosystem, JavaScript has become a widely used programming language for implementing server-side web applications. In this article, we present the first empirical study of static code analysis tools for detecting vulnerabilities in Node.js code. To conduct a comprehensive tool evaluation, we created the largest known curated dataset of Node.js code vulnerabilities. We characterized and annotated a set of 957 vulnerabilities by analyzing information contained in npm advisory reports. We tested nine different tools and found that many important vulnerabilities appearing in the OWASP top-10 are not detected by any tool. The three best performing tools combined only detect up to 57.6% of all vulnerabilities in the dataset, but at a very low precision of 0.11%. Our curated dataset offers a new benchmark to help characterize existing Node.js code vulnerabilities and foster the development of better vulnerability detection tools for Node.js code.